The Use of WhatsApp for Speaking Activities: Teacher’s Voices at Islamic Junior High School - Lenny Marzulina (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2022)
Background: The form of information technology development that can be used as a learning medium during Covid 19 Pandemic is WhatsApp. This WhatsApp is widely used to communicate, both interpersonal communication and group communication. That’s why teachers’ perceptions on the use of WhatsApp in speaking activities needed to be revealed. Methodology: The qualitative method with a case study research design was used in this study. The participants of this study were two teachers of English taken by using total sampling technique. The data obtained from interview were analysed by using thematic analysis. Findings: It was found that (a) WhatsApp could build the students’ interest towards English; (b) WhatsApp made the teachers easier to share speaking materials by using WhatsApp; (c) WhatsApp made the teachers easier to control the class. Meanwhile, the limitations were found that (d) WhatsApp did not build the students’ confidence in speaking English; (e) WhatsApp did not promote students’ independence in learning speaking; (f) WhatsApp did not create enthusiast atmosphere among students; (g) WhatsApp made the students became less active in learning English; (h) WhatsApp did not make the students pay attention to learning English; and (i) WhatsApp persuaded the students to copy-paste the task. Conclusions: Both benefits and limitations were found on the use WhatsApp in speaking activities of as perceived by the teachers. Originality: This study tries to find out teachers’ perceptions on the use of WhatsApp in speaking activities during COVID-19 Pandemic as never been conducted. Keywords : Teachers’ Perceptions, WhatsApp, Speaking Activities